2021
DOI: 10.1093/ofid/ofab575
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects and Antibody Titers in Response to the BNT162b2 mRNA COVID-19 Vaccine in a Prospective Study of Healthcare Workers

Abstract: Background The relationship between postvaccination symptoms and strength of antibody responses is unclear. The goal of this study was to determine whether adverse effects caused by vaccination with the Pfizer/BioNTech BNT162b2 vaccine are associated with the magnitude of vaccine-induced antibody levels. Methods We conducted a single-center, observational cohort study consisting of generally healthy adult participants that we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 28 publications
3
27
2
1
Order By: Relevance
“…Not only high Ab responses against SARS-CoV-2 spike protein but also systemic adverse effects induced by the BNT162b2 vaccine were reported to be more common among participants with preexisting immunity due to COVID-19 infection [ 10 ], suggesting that some systemic adverse effects are induced as a more vigorous response to the SARS-CoV-2 spike protein itself produced by the BNT162b2 vaccine. Previous publications reported that adverse effects induced by the BNT162b2 vaccine had no correlation or only low correlation with Ab titers detected immediately after vaccination [ 5 , 6 , 7 , 8 ]. However, to evaluate the long-term effects of vaccination, research should consider Ab titers several months after vaccination and not only the peak level of Ab titers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only high Ab responses against SARS-CoV-2 spike protein but also systemic adverse effects induced by the BNT162b2 vaccine were reported to be more common among participants with preexisting immunity due to COVID-19 infection [ 10 ], suggesting that some systemic adverse effects are induced as a more vigorous response to the SARS-CoV-2 spike protein itself produced by the BNT162b2 vaccine. Previous publications reported that adverse effects induced by the BNT162b2 vaccine had no correlation or only low correlation with Ab titers detected immediately after vaccination [ 5 , 6 , 7 , 8 ]. However, to evaluate the long-term effects of vaccination, research should consider Ab titers several months after vaccination and not only the peak level of Ab titers.…”
Section: Discussionmentioning
confidence: 99%
“…If the maximum vaccine efficacy, including antibody (Ab) responses, is guaranteed, most people will accept a certain severity of vaccination-related adverse effects [ 2 ]. Although several reports concluded that there is no correlation or only low correlation between adverse effects and the Ab titers detected immediately after vaccination [ 5 , 6 , 7 , 8 ], a correlation is expected between adverse effects and the Ab titers detected several months after vaccination [ 9 ]. Antibody titers alone do not correlate perfectly with protection because the benefits of mRNA vaccines include not only B-cell/humoral responses but also T-cell/cell-mediated immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors influencing the IgG response 10 days after the second vaccine dose, we observed that adverse events are significantly correlated with the antibody titer, as previously suggested by a smaller study on healthy subjects [ 19 ]. Other studies failed to identify a correlation between adverse events and the IgG titers one month following the BNT162b2 vaccination, but the same authors identified sex and body weight as predictors of the incidence of adverse events [ 20 ]. Our data confirm that female gender and younger age are significantly associated with adverse events, and this may reflect the more efficacious immune response observed in women for SARS [ 21 ] and other vaccines [ 22 ], particularly at a younger age.…”
Section: Discussionmentioning
confidence: 99%
“…By 21 January 2022, 60.3% of the world’s population had received at least one COVID-19 vaccine, making it the world’s largest vaccination campaign ever [ 5 ]. However, potential relationship between vaccine-related ARs and immunogenicity has been strongly disputed, poorly investigated and the currently available evidence is contradictory [ 6 , 7 ]. The main objective of the present study was to elucidate the long-term effect of such ARs on antibody production in healthcare workers with and without prior COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%